Marina Rheingantz : terra líquida - Rheingantz, Marina, 1983- (Rio de Janeiro, RJ : Cobogó, 2016)
The book presents an overview of the production of this young Paulista artist. The book, first monographic publication of the painter, brings an essay of curator Rodrigo Moura and and reproduces about of 70 color images of artist's works. In her paintings, Marina Rheingantz performs a process of creation in which constructs and deconstructs screens repeatedly with overlays of paint that form large color fields and, at the same time, enhance individual elements. Desolate landscapes, roads and indoor environments appear only as traces of the real, the fragmented memory in a collage filled with textures.
Text in Portuguese and English.
boek
Keywords: Rheingantz, Marina, -- 1983- -- Criticism and interpretation